DEVELOPMENT PROCESS OF PEDAGOGICAL TECHNOLOGY - Boqiyeva Marjona Shuhratovna (Лучшие интеллектуальные исследования, 2023)
Annotation: at the heart of pedagogical Technologies is the opportunity to fully manage the educational process, analyze it through its design and step-by-step repetition. Modern pedagogy seeks to enter a number of scientific disciplines, the main task for which is to know the accuracy and predictability of the result, the ways to achieve it.